Объяснение:
[tex](x+2015)*((x+2015)^2-1)=(x+2016)*(1-(x+2016)^2).\\[/tex]
Пусть х+2015=t ⇒
[tex]t*(t^2-1)=(t+1)*(1-(t+1)^2)\\t^3-t=(t+1)*(1-t^2-2t-1)\\t^3-t=(t+1)*(-t^2-2t)\ |*(-1)\\t-t^3=(t+1)*(t^2+2t)\\t-t^3=t^3+t^2+2t^2+2t\\2t^3+3t^2+t=0\\t*(2t^2+3t+1)=0\\t_1=x+2015=0\\x_1=-2015.\\2t^2+3t+1=0\\D=1\ \ \ \ \ \sqrt{D}=1\\ t_2=x+2015=-1\\x_2=-2016.\\t_3=x+2015=-0,5\\x_3=-2015,5.\\[/tex]
Ответ: x₁=-2015, x₂=-2016, x₃=-2015,5.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Объяснение:
[tex](x+2015)*((x+2015)^2-1)=(x+2016)*(1-(x+2016)^2).\\[/tex]
Пусть х+2015=t ⇒
[tex]t*(t^2-1)=(t+1)*(1-(t+1)^2)\\t^3-t=(t+1)*(1-t^2-2t-1)\\t^3-t=(t+1)*(-t^2-2t)\ |*(-1)\\t-t^3=(t+1)*(t^2+2t)\\t-t^3=t^3+t^2+2t^2+2t\\2t^3+3t^2+t=0\\t*(2t^2+3t+1)=0\\t_1=x+2015=0\\x_1=-2015.\\2t^2+3t+1=0\\D=1\ \ \ \ \ \sqrt{D}=1\\ t_2=x+2015=-1\\x_2=-2016.\\t_3=x+2015=-0,5\\x_3=-2015,5.\\[/tex]
Ответ: x₁=-2015, x₂=-2016, x₃=-2015,5.